Pengelolaan Dana Desa untuk Pemberdayaan Masyarakat Desa Mulya Subur Kecamatan Pangkalan Lesung Kabupaten Pelalawan - Yunita Dewi Rahmawati; Ratna Dewi; Ainun Mardiah (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
The purpose of this study was to analyze the management of Village Funds for community empowerment in Mulya Subur Village, Pangkalan Lesung District, Pelalawan Regency with the application of village financial management. In this study, the indicators used are village financial management in Permendagri Number 113 of 2015 concerning Village Financial Management in the form of transparency, accountability, participation, and budget discipline and discipline. This type of research is qualitative with the data sources used in the form of primary data and secondary data. Data was collected through observation, interviews, documentation with data analysis techniques through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the management of the Mulya Subur Village Fund has not been carried out optimally as well as the management of the Village Fund. This is because the participatory implementation is still constrained by the lack of community participation in opening up space for participation. In addition, community participation is still passive. In the management of the Village Fund, it is also still focused on physical development activities.